Net neutrality and the incentives (not) to exclude competitors - Ralf Dewenter; Jürgen Rösch (Helmut-Schmidt-Universität - Universität der Bundeswehr Hamburg, Fächergruppe Volkswirtschaftslehre, 2014)
This paper analyses the incentives of a vertical integrated Internet service provider (ISP) to block competitors from content markets. Using a simple model we find that the ISP does not block competing content providers as long as the contents are differentiated sufficiently. Exclusion only takes place when the competitor offers perfect homogeneous content and the ISP has a local monopoly over its Internet access customers or if network effects are strong. In this case, however, the abuse of market power can at least in Europe be prohibited by competition authorities. That is, according to our model there is no need for a regulation of net neutrality.
Keywords: L12; L82; L86; K20; D40; 330; net neutrality; competition; Internet service providers